Maternal obesity and pregnancy outcome a prospective cohort study - Kumar, Ramasamy (2008)
Overweight and obesity are associated with serious social and psychological consequences in addition to the physical health implications. Across the globe obesity has reached an epidemic proportions with almost 1 billion people are either overweight or obese. The incidence of obesity among women in the reproductive age group has increased in concordance with the prevalence in the general population with the reported incidence of obesity during pregnancy varying between 6% and 28%. This has critical consequences for fetal and maternal health in the antepartum, intrapartum and postpartum periods. The aim of the study is to determine the fetalmaternal outcomes in obese pregnant women (antenatally, intrapartum and postpartum) and to compare the adverse outcome between obese and normal weight pregnant women. This is a prospective cohort study carried out in the Obstetrics and Gynecology Department, Hospital Ipoh from October 2005 to October 2006. All pregnant women who booked their pregnancy in Hospital Ipoh and surrounding health clinics before or by 16 weeks of pregnancy were included into this study once they fulfill the inclusion criteria. Once enrolled the progress of the pregnancy was followed up until de/ive1y and six weeks into the postpartum period. The Body Mass Index (BM/), calculated with the help of the weight and height taken between 12 to /6 weeks of pregnancy was taken as the measurement of obesity. The study group were divided into two arms, obese (BMI = 27.5 kglm2 ) and the control group of normal weight mothers (BMI /8.5- 22.9 kg/m2 }. Once the subjects recruited into the study, they undergo routine antenatal care and managed accordingly. The various maternal and fetal outcomes were compiled with the help of a questionnaire. All the data ent1y and analysis were carried out using the social science and statistical packaged (SPSS) version 12. A p value of less than 0. 05 was considered statistically significant. Number of patients enrolled in this study is 1200 with obese mothers represent 50% of the study sample. There is no significant difference (p < 0.05) in the mean age between the two study groups. The bulk of the studied population were Malays (59.3%) but when analysed individually the highest prevalence of obesity (59.9%) was noted among the Indian mothers. Majority of the study population in the obese category were multiparas (66. 7%) where else the normal weight categ01y consist of almost equal number of primi (49.5%) and multigravida's (46.3%). This difference was found to be statistically significant (p < 0.001). There is an higher incidence of Diabetic Mellitus (30.8%) among the family members of the obese mothers as compared to mothers in the normal weight categmy (17.2%) which is significant {p < 0.001). Using a multivariate analysis even after adjusted for the possible confounders the following conditions were significantly associated with maternal obesity [quoted as adjusted odds ratio (OR) and 95% confidence interval (Cl)} : incidence of abortion (OR : 1.09 ; 95% CJ : 0.81-1.48), incidence of Gestational Hypertension and Pre-eclampsia (OR : 6.93; 95% CJ: 4.60- 10.44), incidence of Gestational Diabetic Mellitus (OR : 3.48 ; 95% CJ : 2.43-4.97), incidence of Caesarean deliveries (OR: 2.65; 95% CI: 1.91-3.69), rate of augmentation of labour (OR : 2.20 ; 95% CI: 1.56-3.12) and incidence of delivering macrosomic baby (OR : 3.52 ; 95% CI : 2.15-5. 76). No significant differences were noted between the two groups in terms of non spontaneous rupture of membrane, postdatism, labour induction, instrumental delivery, third or fourth degree perineal tear, postpartum haemorrhage, thromboembolism and perinatal complications such as prematurity, shoulder dystocia, low Apgar scores, neonatal intensive care unit admission, meconium aspiration and perinatal mortality. There was also an increasing trends of adverse fetalmaternal outcomes in relation to the severity of the degree of obesity. Maternal obesity in early pregnancy is an independent risk factor for a number of adverse obstetric outcomes and is significantly associated with an increased incidence of macrosomic baby.